Coiled‐coil registry shifts in the F684I mutant of Bicaudal D result in cargo‐independent activation of dynein motility. (28th June 2020) - Cui, Heying; Ali, M. Yusuf; Goyal, Puja; Zhang, Kaiqi; Loh, Jia Ying; Trybus, Kathleen M.; Solmaz, Sozanne R.
Abstract: The dynein adaptor Drosophila Bicaudal D (BicD) is auto‐inhibited and activates dynein motility only after cargo is bound, but the underlying mechanism is elusive. In contrast, we show that the full‐length BicD/F684I mutant activates dynein processivity even in the absence of cargo. Our X‐ray structure of the C‐terminal domain of the BicD/F684I mutant reveals a coiled‐coil registry shift; in the N‐terminal region, the two helices of the homodimer are aligned, whereas they are vertically shifted in the wild‐type. One chain is partially disordered and this structural flexibility is confirmed by computations, which reveal that the mutant transitions back and forth between the two registries. We propose that a coiled‐coil registry shift upon cargo‐binding activates BicD for dynein recruitment. Moreover, the human homolog BicD2/F743I exhibits diminished binding of cargo adaptor Nup358, implying that a coiled‐coil registry shift may be a mechanism to modulate cargo selection for BicD2‐dependent transport pathways. Abstract : The dynein adaptor Drosophila Bicaudal D (BicD) is auto‐inhibited and activates dynein motility only after cargo is bound. In contrast, we show that the full‐length BicD/F684I mutant activates dynein processivity even in the absence of cargo. Our X‐ray structure of the C‐terminal domain of the BicD/F684I mutant and our molecular dynamics simulations provide insights into the molecular mechanism that activates the adaptor Bicaudal D for dynein recruitment; these transport pathways are important for brain development and cell cycle control.